Bibliometric Analysis of Publication Activity in the Field of GIANT Cell Arteritis: A SCOPUS-based Study - Bareeqa, Syeda Beenish; Samar, Syeda Sana; Kamal, Sufiyan; Khan, Fizza Zaman; Shakeel, Hafsa; Ali, Kanza; Humayun, Syed Hasham; Ahmed, Syed Ijlal (TH Open, 2022)
Objective Giant cell arthritis (GCA) is a type of vasculitis which is more common in female gender and is closely associated with Polymyalgia rheumatic. One of its important complication include visual impairment. The burden of disease is expected to be very high by 2050 and there is a need to compile the data on most influential studies on GCA to define future strategy to deal with this dangerous disease. Bibliometrics is a statistical analysis of published literature that reflects the value and impact of a particular publication within the specific field. Aim of our study is identify the most significant contributors and their quality of contribution in the field.Method We conducted this analysis utilizing SCOPUS database using different related MeSH terms. After a detailed screening, the list of top-50 articles were presented in the results in descending order of their ranks on the basis of their total number of citation. Most of our data comprises of publications from 1971–2012.Result The top-50 most cited articles on GCA were published between 1971 and 2012 with the median number of citations 274 ranging from 598–187. Annals of Internal Medicine was the top ranked journal with 13 publications from the list. The highly ranked author based on the number of publications was Hunder GG (20 publications) with h-index of 40, retaining affiliation with Mayo Clinic, Rochester, United States. Mayo Clinic was the most frequently mentioned institute among the affiliations. The United States was found to be the most productive country rendering most of the articles (64%).Conclusion Our bibliometric analysis on Giant cell arteritis identifies the information which may direct future research contributions, identify field experts, guide researchers to fill knowledge gaps, and assist in research fund allocation.
Keywords: bibliometric; citation classics; vasculitis; giant cell arteritis; temporal arteritis; polymyalgia rheumatic